The tragic vision of African American religion - Johnson, Matthew V., 1961- (Black religion, womanist thought, social justice., 2010)
This phenomenological analysis of African American religious subjectivity suggests the tragic, understood as an ontological category, as the seminal hermeneutical lens through which one can deepen one's understanding of the experience and its theological implications. New insights garnered from this framework challenges many traditional theological assumptions leading to the decentralization of the resurrection as the key Christian symbol. Through the abstract African American longing, Johnson connects the resurrection and the cross in one dialectically constituted moment of a larger recalibration of Christian categories, which brings the "Second Coming" into new theological and philosophical prominence.